The Concept of Islamic Parenting in the Era of Islamic Moderation: An Analysis of Hurlock's Parenting Theory - Vivi Yulia Nora (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
AbstractThis article describes the parenting proposed by Hurlock and its relevance to parenting in Islam in the face of Islamic moderation demands. This research is comparative research with data analysis techniques using content analysis and descriptive analysis. This research concludes that there are two Hurlock’s parenting patterns related to Islamic parenting, namely authoritarian and democratic parenting. In Islamic Parenting, parents parenting is not authoritarian and not too permissive towards children; this is in line with the concept of Wasatiyyah in Islam, which means in the middle. This parenting is one of the examples of Noah AS., Ibrahim AS., and Luqman as told int the Qur’an, and the example og prophet Muhammad SAW., in the Sunnah. To face the moderation of Islam, parents can apply these two parenting styles to their children. Through moderate but still Islamic parenting, it is hoped that it can make a generation that can become part of the